Determination of Severity of Murine IgA Nephropathy by Glomerular Complement Activation by Aberrantly Glycosylated IgA and Immune Complexes - Hashimoto, Azusa (American Society for Investigative Pathology, 2012)
The pathogenic roles of glomerular deposition of components of the complement cascade in IgA nephropathy (IgAN) are not completely clarified. To investigate the pathologic role of complement pathways in IgAN, two IgAN-prone mouse models were examined. Grouped ddY (gddY) mice showed significant high proteinuria, severe glomerular lesions, and extracellular matrix expansion compared with high serum IgA (HIGA) mice but with similar intensity of glomerular IgA deposition. Glomerular activation of the classical, lectin, and alternative pathways was demonstrated by significantly stronger staining for complement (C)3, C5b-9, C1q, C4, mannose-binding lectin (MBL)-A/C, MBL-associated serine protease-2, and factor B and properdin in gddY mice than in HIGA mice. Similarly, the serum levels of IgA-IgG2a/IgM and IgA–MBL-A/C immune complexes and polymeric IgA were significantly higher in gddY mice than in HIGA mice. Moreover, the serum levels of aberrantly glycosylated IgA characterized by the binding of Sambucus nigra bark lectin and Ricinus communis agglutinin I were significantly higher in gddY mice than in HIGA mice. This aberrancy in glycosylation was confirmed by monosaccharide compositional analysis of purified IgA using gas-liquid chromatography. This study is the first to demonstrate that aberrantly glycosylated IgA may influence the formation of macromolecular IgA including IgA-IgG immune complexes and subsequent complement activation, leading to full progression of IgAN.